2013
DOI: 10.6007/ijarbss/v3-i12/415
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Stirring Purchase Intention of Smartphone among Adolescents in Perlis

Abstract: In recent years, mobile phone has evolved from essentially an interpersonal communication device to a multimedia machine known as "smartphone". The usage rate of smartphone in Malaysia is still slow comparing to her neighbour, Singapore. Among all states in Malaysia, Perlis was reported to be the lowest smartphone users. This study attempts to investigate the antecedents that shaped the purchase intention of smartphone among adolescents in Perlis. A total of 379 close-ended questionnaires were distributed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
0
19
1
2
Order By: Relevance
“…Before buying a cellular phone, young consumers' often thinks of whether their friends, family members or peers like it. In many previous studies, social influence has been confirmed as having significant influence on consumer's cellular phone purchase decision (Ibrahim, Subari, Kassim & Mohamood, 2013;Suki, 2013;Uddin et al, 2015). Hence, the researcher proposed the following hypothesis: H4: Social influence has significant influence on university students' cellular phone purchase intention.…”
Section: Social Influencementioning
confidence: 93%
“…Before buying a cellular phone, young consumers' often thinks of whether their friends, family members or peers like it. In many previous studies, social influence has been confirmed as having significant influence on consumer's cellular phone purchase decision (Ibrahim, Subari, Kassim & Mohamood, 2013;Suki, 2013;Uddin et al, 2015). Hence, the researcher proposed the following hypothesis: H4: Social influence has significant influence on university students' cellular phone purchase intention.…”
Section: Social Influencementioning
confidence: 93%
“…Future possibility and willingness of individuals for purchasing a good or service is said to be the purchase intention (Richard, Loury & David, 2013). According to Ibrahim, Kassim, & Mohamood (2013) social influence has high impact in attracting young consumers for buying Smartphone and the buyers collect brand information from different sources like colleagues, friends and family and so on and then they will decide about their brand choice. It is identified by the previous research that there are positive relationships between brand image, peer influence, product feature and price, with purchase intention (Lin & Lin, 2007;Ibrahim, Kassim, & Mohamood, 2013).…”
Section: Purchase Intentionmentioning
confidence: 99%
“…According to Ibrahim, Kassim, & Mohamood (2013) social influence has high impact in attracting young consumers for buying Smartphone and the buyers collect brand information from different sources like colleagues, friends and family and so on and then they will decide about their brand choice. It is identified by the previous research that there are positive relationships between brand image, peer influence, product feature and price, with purchase intention (Lin & Lin, 2007;Ibrahim, Kassim, & Mohamood, 2013). (Dodds et al, 1998;Schiffman & Kanuk, 2000;Yang, 2009) according to Dodds (1998) and Schiffman & Kanuk (2000) if consumers have higher willingness to purchase a product they will have a higher purchase intention.…”
Section: Purchase Intentionmentioning
confidence: 99%
“…http: //www.ijmp.jor.br v. 11, n. 3, May-June 2020ISSN: 2236-269X DOI: 10.14807/ijmp.v11i3.1076 Furthermore, the effort required to acquire smartphones and consumer understanding of the benefits of using smartphones is also two factors that have a significant effect on the intention to buy (IBRAHIM et al, 2013). Perceptual value is one of the factors that can stimulate the intention to buy; perceived value comes from relative advantages and product compatibility compared to the effort required to get a product.…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%